(untitled) (SAARC Journal of Agriculture, 2014)
Leaf blight of caused by Pseudomonas syringae pv. syringae is a severe disease of litchi saplings, which is considered as a threat for raising healthy sapling of the fruit in Bangladesh. A survey was conducted to find out incidence and severity of the disease in five regions of Bangladesh namely Rajshahi, Dinajpur, Mymensingh, Barishal and Khagrachari. The highest disease incidence was recorded in Dinajpur and Kagrachari regions and the lowest in Mymensingh region. On the other hand, the highest disease severity was found in Dinajpur and Kagrachari regions and the lowest in Mymensingh region. Another experiment was conducted to determine genetic diversity of the causal bacterium following molecular study. Twenty five diseased samples of bacterial leaf blight of litchi were collected from 25 locations in five regions and one isolate of P. syringae pv. syringae was isolated from each sample. The values of pair-wise comparisons of Neis (1972) genetic distance among5 different locations of P. syringae pv. syringae were computed. From the UPGMA dendrogram drawn on the basis of Neis (1972) genetic distances and comparatively the highest genetic distance (0.9163) was observed in Khajrachari vs Barishal, Mymensingh vs Barishal and Rajshahi vs Mymensingh but Dinajpur was close to the Barishal with the least genetic distance (0.3567). Thus, the results indicate that remarkable genetic diversity exists among the isolates of P. syringae pv. syringae from different origins Bangladesh. DOI: http://dx.doi.org/10.3329/sja.v12i1.21121 SAARC J. Agri., 12(1): 150-161 (2014)